Efektivitas Penggunaan Media Pembelajaran Interaktif Berbasis Wordwall dalam Meningkatkan Pemahaman Konsep Matematika Siswa Sekolah Dasar - Nurul Siti Kotimah; Aqidatul Munfariqoh; Anna Mariyani (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
The Efficiency of Employing Wordwall-Based Interactive Educational Tools in Enhancing Elementary Students’ Comprehension of Math Concepts. In the digital age, the educational curriculum needs to evolve to cater to the requirements of Generation Alpha. At the primary school stage,many learners find mathematics challenging due to its abstract and deductive characteristics. Research conducted at SDN 1 Nglebur and SDN 2 Ngawen indicated that the absence of an effective unteractive learning framework led to poor academic performance among students, with mastery rates of only 32.14% and 40%, respectively. This research sought to assess the efficacy of Wordwall media in bolstering fifth-grade pupils’ grasp of mathematical ideal, particularly concerning LCM and GCF topics. A quasi-experimental framework and a quantitative methodology were employed in the investigation. The sample comprised 28 students from the experimental group and 30 from the control group. Information was gathered through experimentation involving pretest and posttests. Results from the experimental group demonstrated a notable improvement,exhibiting an average increase of 25.35 points, which was significantly greater that the control group at a significance level of 0.0002 (less that 0.05). Moreover, the avarage N-Gain value recorded for the experimental group was 0.41, while the control group only achieved 0.01. Learning materials developed with Wordwall are effective in enhancing fifth graders’ understanding of mathematics. The gamification aspects and interactive functionalities of the platform have been shown to convert abstract material into a more visual and engaging format, leading to a notable boost in student motivation and educational results. The study’s conclusion indicates that Wordwall, serving as an interactive educational platform, can assist in elucidation abstract concepts and elevating learning enthusiasm through gamification elements, providing educator with empirical support for incorporating technology into elementary mathematics instruction.